Governing in the Anthropocene: What Future Systems Thinking in Practice?†. (September 2016) - Ison, Ray
Abstract : The revealing and concealing features of the metaphor 'earth as Anthropocene' are explored in an inquiry that asks: In the Anthropocene what possible futures emerge for systems thinking in practice? Framing choice, so important yet so poorly realised, is the starting point of the inquiry. Three extant conceptual pathway‐dependencies are unpacked: governance or governing; practice or practising and 'system'. New data on the organisational complexity within the field of cybersystemics is presented; new 'imaginaries' including systemic co‐inquiry and institutional recovery are proposed as novel institutions and practices to facilitate systemic transformations within an Anthropocene setting. The arguments of the paper are illustrated through a research case study based on attempts to transform water and/or river situations towards systemic water governance. It is concluded that future systems research can be understood as the search for effective 'imaginaries' that offer fresh possibilities within an Anthropocene framing. Copyright © 2016 John Wiley & Sons, Ltd.